Aerobic fitness modulates the association between APOE genotypes and serum lipemia in adolescents - Maria Fátima Glaner; Thales Boaventura Rachid Nascimento; Otávio de Tôledo Nóbrega (Universidade Estadual Paulista (UNESP), 2014)
The purpose of this study was to analyze the association between APOE alleles and serum lipemia in adolescents with low and adequate aerobic fitness. The sample was comprised of 105 boys and 151 girls (49% and 46% from rural area) of European ancestry, aged 11 to 17 years, and classified according to: 1) APOE genotype: group ε2 (ε2/3+ε2/2), ε3 (ε3/3), and ε4 (ε3/4+ε4/4); 2) aerobic fitness: adequate or low; 3) serum lipemia: elevated total cholesterol (TC), low-density lipoprotein (LDL) and triglycerides, and low high-density lipoprotein (HDL). The results showed that aerobic fitness modulates the association between APOE alleles and serum lipemia in adolescents, suggesting that adequate aerobic fitness levels exert a greater effect of reducing TC and LDL in ε2 carriers, as well as of increasing HDL and reducing triglycerides in ε3 and ε4 carriers.